Unambiguous velocity estimation method based on intra‐pulse cross‐correlation. Issue 6 (29th April 2020) - Zhang, Yunjian; Pan, Pingping; Fu, Maozhong; Deng, Zhenmiao; Zhang, Yixiong; Liu, Hui
Abstract : In this study, by employing the intra‐pulse cross‐correlation (IPCC) operation, an unambiguous velocity estimation method is proposed for narrow‐band long‐range radars with high carrier frequency and low pulse repetition frequency. This estimation algorithm is simple and could be easily implemented in existing radar systems without changing the radar hardware or the pulse transmitting scheme. Comparing with the slow time dimension correlation algorithm, the accuracy of the proposed intra‐pulse frequency domain method is greatly improved, and the brute‐force search for the unknown motion parameters is also unnecessary. By first setting a small frequency offset of the IPCC operation, the unambiguous velocity region could be significantly enlarged. Using the relatively coarse but unambiguous estimates and increasing the frequency offset step by step, the IPCC is repeatedly applied to obtain more accurate estimates. Note that the estimation results of the IPCC algorithm could be used in the maximum‐likelihood estimator for ambiguity resolution. The Cramér‐Rao bound for the proposed algorithm is derived, and the optimal frequency offset in the sense of estimation accuracy is also analysed. Through numerical simulations for both synthetic and real radar data, the effectiveness of the proposed estimation algorithm is verified.